Acting: Basic Techniques - Rai, Parshuram (Prajnik Bimarsha प्राज्ञिक विमर्श, 2025)
This article examines the acting of actors with a focus on the role of technique in their craft, which plays much significant to actor while acting. The study explores various acting techniques through a comprehensive approach that includes field studies, direct correspondence with actors, discussions with thematic experts, book references, and the researcher's own acting experience and perceptual methods. By integrating these diverse sources, the article aims to provide an in-depth analysis of how acting techniques are applied and their significance in enhancing the art of performance.